Fluid-Structure Interaction in Microchannel Using Lattice Boltzmann Method and Size-Dependent Beam Element (Advances in Applied Mathematics and Mechanics, 2014)
Fluid-structure interaction (FSI) problems in microchannels play prominent roles in manyengineering applications. The present study is an effort towards the simulation of flowin microchannel considering FSI. Top boundary of the microchannel is assumed to be rigidand the bottom boundary, which is modeled as a Bernoulli-Euler beam, is simulated bysize-dependent beam elements for finite element method (FEM) based on a modified couplestress theory. The lattice Boltzmann method (LBM) using D2Q13 LB model is coupled to theFEM in order to solve fluid part of FSI problem. In the present study, the governingequations are non-dimensionalized and the set of dimensionless groups is exhibited toshow their effects on micro-beam displacement. The numerical results show that thedisplacements of the micro-beam predicted by the size-dependent beam element aresmaller than those by the classical beam element.